Deposition, Incubation Period and Hatching of Eggs from Triatoma juazeirensis Costa & Felix and Triatoma sherlocki Papa, Jurberg, Carcavallo, Cerqueira & Barata, (Hemiptera: Reduviidae) under Laboratory Conditions - Neiva, Vanessa Lima; Gumiel, Marcia; Lima, Marli Maria; Gonçalves, Teresa Cristina Monte; Provance, David William; Almeida, Carlos Eduardo; Costa, Jane (EntomoBrasilis, 2012)
Triatoma juazeirensis Costa & Felix and Triatoma sherlocki Papa, Jurberg, Carcavallo, Cerqueira & Barata are members of the Triatoma brasiliensis Neiva, 1911 species complex. Discovered in the state of Bahia, Brazil, collections from both natural and artificial habitats revealed that they can be found infected by Trypanosoma cruzi (Chagas) suggesting a potential to be vectors for Chagas disease. To contribute to the evaluation of this potential, the capacity of each species to proliferate under laboratory conditions was measured by the number of eggs laid, the rate of hatching and the incubation time over a 22-week period. Thirty pairs, fifteen of each species, were maintained under laboratory conditions by weekly feedings on mice, Mus musculus (Linnaeus). The comparisons of laid and hatched eggs of T. juazeirensis and T. sherlocki were analyzed by t-test and Mann-Whitney test. When p value of <0.01 it was considered statistically significant. For comparison of the average longevity, a chi-square analysis was used. When p > 0.01, the average longevity was not considered statistically different. The two species presented similar incubation periods for their eggs, but T. juazeirensis demonstrated greater reproductive potential than T. sherlocki. The females of T. sherlocki deposited significantly fewer eggs with a lower rate of viability. Results suggest that T. juazeirensis is a more serious threat, concerning to these reproductive features. Considering the longevity, no significant differences could be noticed. Oviposição, Período de Incubação e Eclosão dos Ovos de Triatoma juazeirensis Costa & Felix e Triatoma sherlocki Papa, Jurberg, Carcavallo, Cerqueira & Barata (Hemiptera: Reduviidae) em Condições de Laboratório Resumo. Triatoma juazeirensis Costa & Felix e Triatoma sherlocki Papa, Jurberg, Carcavallo, Cerqueira & Barata são membros do complexo de espécies Triatoma brasiliensis Neiva, 1911. Descobertas no estado da Bahia, Brasil, coletas em ambos os habitats natural e artificial revelaram que essas espécies são encontradas naturalmente infectadas por Trypanosoma cruzi (Chagas) sugerindo que ambos os vetores estão, provavelmente, associados à transmissão da doença de Chagas na região. Com o objetivo de contribuir para avaliação da capacidade vetorial das duas espécies, parâmetros biológicos como: fecundidade, fertilidade, período de incubação dos ovos e longevidade das fêmeas foram analisados comparativamente. Trinta casais individualizados, 15 de T. juazeirensis e 15 de T. sherlocki, foram alimentados em camundongos Mus musculus (Linnaeus) semanalmente e mantidos sob condições ambientais. Os ovos foram coletados e individualizados em frascos separados por data de postura até a eclosão das ninfas. A comparação das médias da oviposição e da eclosão de T. juazeirensis e T. sherlocki foi realizada pelo test T seguida do test de Mann-Whitney, quando p<0,01 a diferença foi considerada estatisticamente significativa. Para comparação das médias de longevidade aplicou-se o teste Qui-quadrado, quando p>0,01 as médias de longevidade não foram consideradas estatisticamente diferentes. As duas espécies apresentaram períodos similares de incubação dos ovos, entretanto, T. juazeirensis demonstrou maior potencial reprodutivo, com fecundidade e fertilidade superiores a T. sherlocki, em condições de laboratório. Quanto à longevidade, as fêmeas de T. sherlocki e T. juazeirensis não apresentaram diferenças significativas.